Sexual harassment in Malaysian educational institutions: causes and solutions - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Trakic, Adnan; Mallow, Muzaffar Syah; Surajudeen, Ahmad Tijani (International Organisation Centre of Academic Research, 2014)
The vitality of schools in proffering solutions to the societal challenges cannot be underrated. However, school as a hub and pivot place in addressing multifarious challenges in our society is faced with some social ills such as bullying and sexual harassment. An escalation of sexual harassment in schools' and on campuses cannot be denied. The greater challenge is inadequacy and ineffective measures to curb prevalence of sexual harassment. More so, there are only a few existing guidelines in combating sexual harassment such as the Penal Code, Employment Act and the Code of Conduct for Industrial Harmony. However, there is yet to be a proper academic focus providing an effective mode of minimizing the prevalence of sexual harassment in schools and institutions of higher learning by formulating a policy and procedure in eschewing sexual harassment in schools in particular, and society in general in Malaysia. Hence, this paper elaborately explicates the various issues relating to sexual harassment in the Malaysian schools and institutions of higher learning and further, the suggested approaches towards its prevention.